Prediction of lisinopril pediatric dose from the reference adult dose by employing a physiologically based pharmacokinetic model - Memoona Rashid; Muhammad Sarfraz; Mosab Arafat; Amjad Hussain; Nasir Abbas; Muhammad Waqas Sadiq; Muhammad Fawad Rasool; Nadeem Irfan Bukhari (BMC, 2020)
Abstract Background This study aimed to assess the pediatric lisinopril doses using an adult physiological based pharmacokinetic (PBPK) model. As the empirical rules of dose calculation cannot calculate gender-specific pediatric doses and ignores the age-related physiological differences. Methods A PBPK model of lisinopril for the healthy adult population was developed for oral (fed and fasting) and IV administration using PK-Sim MoBI® and was scaled down to a virtual pediatric population for prediction of lisinopril doses in neonates to infants, infants to toddler, children at pre-school age, children at school age and the adolescents. The pharmacokinetic parameters were predicted for the above groups at decremental doses of 20 mg, 10 mg, 5 mg, 2.5 mg, and 1.5 mg in order to accomplish doses producing the pharmacokinetic parameters, similar (or comparable) to that of the adult population. The above simulated pediatric doses were compared to the doses computed using the conventional four methods, such as Young's rule, Clark's rule, and weight-based and body surface area-based equations and the dose reported in different studies. Results Though the doses predicted for all subpopulations of children were comparable to those calculated by Young's rule, yet the conventional methods overestimated the pediatric doses when compared to the respective PBPK-predicted doses. The findings of previous real time pharmacokinetic studies in pediatric patients supported the present simulated dose. Conclusion Thus, PBPK seems to have predictability potential for pediatric dose since it takes into consideration the physiological changes related to age and gender.